Disability-adjusted life years for acute bronchiolitis in infants in Colombia (2021)
ABSTRACT: Introduction: acute bronchiolitis is the leading cause of hospitalization in infants worldwide. However, little is known about the real impact of on society in terms of years of life lost due to this condition. The objective of the present study is to determine the Disability-Adjusted Life Years (DALYs) for acute bronchiolitis in infants in Colombia. Methods: data from the national epidemiological surveillance system were used to estimate DALYs, calculated from the sum of years of life lost and years lived with disability due to acute bronchiolitis in Colombia. A bootstrapped method with 10,000 iterations was used to estimate each statistical parameter using the package DALYs calculator in R. Results: in 2019, 447,434 years of life (confidence interval 95% 397,647- 512,759) were lost due to acute bronchiolitis in Colombian infants. The estimated rate was 34 DALYs/1000 person-year (95% confidence interval 30-39). Conclusion: our paper shows the high burden of disease associated with bronchiolitis in Colombia. Prevention strategies, such as acute bronchiolitis vaccination, to reduce morbidity associated with acute bronchiolitis should be encouraged in our country.